2011
DOI: 10.1136/emj.2010.106500
|View full text |Cite
|
Sign up to set email alerts
|

Acute intoxication patients presenting to an emergency department in the Netherlands: admit or not? Prospective testing of two algorithms

Abstract: The algorithms had good sensitivity and better specificity than current clinical practice in most hospitals. It is too early to advocate their implementation, but results indicate that it is possible to use clinical parameters objectively to reduce unnecessary admissions to the ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…[20][21][22] Furthermore, there has been some modest development in creating new prediction models, of which the Dutch study performed by Ambrosius et al is most comparable to our study. [23] The authors tested a prediction model, based on literature research and expert opinion, and determined the general need for hospital admission for intoxicated patients …”
Section: Mechanical Venɵlaɵon N=1970 Cpr N=120mentioning
confidence: 99%
“…[20][21][22] Furthermore, there has been some modest development in creating new prediction models, of which the Dutch study performed by Ambrosius et al is most comparable to our study. [23] The authors tested a prediction model, based on literature research and expert opinion, and determined the general need for hospital admission for intoxicated patients …”
Section: Mechanical Venɵlaɵon N=1970 Cpr N=120mentioning
confidence: 99%
“…In accordance to literature, alcohol was the most prevalent intoxication in our study. [2,49] In the current study, a co-intoxication was present in almost one third of all alcohol intoxicated patients. This is higher compared to other studies where alcohol is more often seen as a mono intoxication, although higher rates of combination intoxications are reported.…”
Section: Discussionmentioning
confidence: 47%
“…The occurrence of all intoxications treated in the ED found in this study is higher than those found in literature in the Netherlands. [1,4] Possible explanations could be a higher alcohol and/or drug use in the population over time, a higher use of alcohol and/or drugs in the population in Rotterdam, and/or the inner city hospital location of this study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations